Dittrichia viscosa (L.) Greuter (Asteraceae): Nuevo registro para la flora introducida de Chile - NOVOA, PATRICIO (Gayana Botánica, 2017)
Dittrichia viscosa is recorded for the first time in Chile as an introduced species. A brief description with photographs and, agrological antecedents are presented.